EFEKTIFITAS PENGGUNAAN SISTEM INFORMASI MANAJEMEN NIKAH (SIMKAH) DALAM MENINGKATKAN PELAYANAN ADMINISTRASI PERNIKAHAN DIKANTOR URUSAN AGAMA KECAMATAN TAMANSARI KABUPATEN BOGOR - Assyfo Raudah Putri; Layla Luna Marina; Zivana Zhafira Aziz; Khairunnisa (STKIP Subang, 2026)
The development of information technology has encouraged the digitalization of public services, including marriage administration services through the Marriage Management Information System (SIMKAH) at the Office of Religious Affairs (KUA). This study aims to analyze the effectiveness of SIMKAH in marriage administration services at the KUA of Tamansari District and to identify the challenges encountered in its implementation. This study employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of SIMKAH has been effective, as reflected in faster services, improved data accuracy through integration with the Directorate General of Population and Civil Registration (Dukcapil), secure data management, and easier retrieval of marriage records. However, several challenges remain, including internet network disruptions, data entry errors, limited public digital literacy, and the continued role of Marriage Registration Assistants (P3N) in supporting the registration process. Therefore, improvements in network infrastructure, staff competence, and public outreach are necessary to optimize the implementation of SIMKAH.